Workshop Merancang Modul Ajar dengan Pendekatan Pembelajaran Mendalam (Deep Learning) Menggunakan AI pada Guru Biologi SMA/MA Kota Parepare - Jafar, Jusmiati; Muadyah, Afifah Afra; Yusran, Ali Akbar Firdaus; Silas, Erika Immanuela; Amalia, Putri; Yunandar (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This activity aims to enhance the understanding of Biology teachers at the senior high school level (SMA/MA) in Parepare City regarding the deep learning approach based on artificial intelligence (AI). The implementation involved 11 participants from the MGMP Biology group, using methods such as material presentation, simulation of lesson module design, and evaluation through questionnaires and interviews. The results showed that 81.8% of participants understood the concept of deep learning; however, its practical implementation remained limited (9.1%). The participant satisfaction level reached 72.5%, indicating the success of the workshop in enriching teachers' pedagogical literacy and practical skills. This workshop contributed to bridging the gap between theory and practice and promoted innovation in designing AI-based teaching modules. The recommendations highlight the importance of continuous training and the development of technology-based learning resources to support educational transformation in the digital era.